BIOM-01. MTH1 EXPRESSION IS UPREGULATED IN BRAIN METASTASES OF MALIGNANT MELANOMA. (12th November 2021) - Timmer, Marco; Timmer, Marco; Kuhl, Saskia; Goldbrunner, Roland
Abstract: MuT Homolog1 (MTH1) is an enzyme involved in DNA repair in normal cells and is often up-regulated in cancer cells. The enzyme catalyses the hydrolysis of oxidised dNTPs, to prevent their incorporation into DNA or RNA, resulting in mutations or cell damage/death. Cancer cells can have a high concentration of ROS, due to defective redox regulation. This results in the damage of DNA and oxidises free dNTPS, which in turn leads to mutations in DNA replication or cell death. The quantification of MTH1 expression was done by Western Blot analysis. 16 tumours were obtained during neurosurgery, 8 metastatic and 8 recurrent tumours of the same patient, and immediately frozen using liquid nitrogen. The proteins were extracted using RIPA lysis buffer. Western Blot was performed and detection followed via peroxidase linked secondary antibodies. MTH1 expression was shown to be up-regulated in brain metastases (1, 442+/-0, 6374) versus normal brain tissue (0, 4133+/-0, 277). However, in the recurrent tumour of the brain metastases, MTH1 was not expressed in a significantly higher amount compared the control tissue and less than in the brain metastases (0, 6941+/-0, 4146). The high expression of MTH1 in cerebral metastases presents a therapeutic target for MTH1-inhibitors, provided these are able to cross the blood brain barrier. Comparison to the primary melanoma tumour would be useful in showing significant differences of the metastases. Lower levels of MTH1 in recurrent brain metastases may suggest dedifferentiation from the original metastases. It may present a target for specific treatment of brain metastases of melanoma.